A vari-stiffness nonlinear isolator with magnetic effects: Theoretical modeling and experimental verification. (November 2018) - Yan, Bo; Ma, Hongye; Zhao, Chenxue; Wu, Chuanyu; Wang, Ke; Wang, Pengfei
Highlight: A novel vari-stiffness nonlinear isolator is designed, modeled, and tested. The nonlinear stiffness can be adjusted and optimized with adjustable devices. Repulsive force acts as a softening spring to increase the isolation bandwidth. Experimental results validate the excellent nonlinear isolation performance. Abstract: Nonlinear isolators can decrease dynamic stiffness and thus enhance vibration isolation performance. This paper presents a novel passive vari-stiffness nonlinear isolator with the magnetic repulsive force and magnetic attractive force effects. The isolator consists of a passive mass-spring-damper element and a nonlinear magnetic coupling element. The nonlinear magnetic coupling element contains three moving ring permanent magnets and three fixed ring magnets. The fixed magnets assembled separately at the three adjustable devices that are uniformly distributed along the circumference. The expression of the nonlinear magnetic force is obtained according to the Amperian current model, and the corresponding equivalent nonlinear magnetic stiffness is derived and approximated. The governing equation of the proposed isolator is established and the transmissibility is analyzed with the harmonic balance method. The experiment was set up to verify both the theoretical model and simulations. Both the numerical and experimental results point out that the repulsive force serves as a softening spring to enhance the isolation performance at the higher frequency, while the attractive force serves as a hardening spring to improve the isolation performance at a relative lower frequency bandwidth. Graphical abstract: